Transcriptome Analysis and Knockdown of the Juvenile Hormone Esterase Gene Reveal Abnormal Feeding Behavior in the Sugarcane Giant Borer - Noriega, Daniel D.; Arraes, Fabricio B. M.; Antonino, José Dijair; Macedo, Leonardo L. P.; Fonseca, Fernando C. A.; Togawa, Roberto C.; Grynberg, Priscila; Silva, Maria C. M.; Negrisoli, Aldomario S.; Grossi-de-Sa, Maria F. (Frontiers in Physiology, 2020)
The sugarcane giant borer (SGB), Telchin licus licus, is a pest that has strong economic relevance for sugarcane producers. Due to the endophytic behavior of the larva, current methods of management are inefficient. A promising biotechnological management option has been proposed based on RNA interference (RNAi), a process that uses molecules of double-stranded RNA (dsRNA) to specifically knock down essential genes and reduce insect survival. The selection of suitable target genes is often supported by omic sciences. Studies have shown that genes related to feeding adaptation processes are good candidates to be targeted by RNAi for pest management. Among those genes, esterases are highlighted because of their impact on insect development. In this study, the objective was to evaluate the transcriptome responses of the SGB’s gut in order to provide curated data of genes that could be used for pest management by RNAi in future studies. Further, we validated the function of an esterase-coding gene and its potential as a target for RNAi-based control. We sequenced the gut transcriptome of SGB larvae by Illumina HiSeq and evaluated its gene expression profiles in response to different diets (sugarcane thatch and artificial diet). We obtained differentially expressed genes (DEGs) involved in detoxification, digestion and transport, which suggests a generalist mechanism of adaptation in SGB larvae. Among the DEGs, was identified and characterized a candidate juvenile hormone esterase gene (Tljhe). We knocked down the Tljhe gene by oral delivery of dsRNA molecules and evaluated gene expression in the gut. The survival and nutritional parameters of the larvae were measured along the developmental cycle of treated insects. We found that the gene Tljhe acts as a regulator of feeding behavior. The knockdown of Tljhe triggered a forced starvation state in late larval instars that significantly reduced the fitness of the larvae. However, the mechanism of action of this gene remains unclear, and the correlation between the expression of Tljhe and the levels of JH metabolites in the hemolymph of the SGB must be assessed in future research.